Squeezing for Life – Properties of Red Blood Cell Deformability - Huisjes, Rick; Bogdanova, Anna; van Solinge, Wouter W.; Schiffelers, Raymond M.; Kaestner, Lars; van Wijk, Richard (Frontiers in Physiology, 2018)
Deformability is an essential feature of red blood cells (RBCs) that enables them to travel through even the smallest capillaries of the human body. Deformability is a function of (i) structural elements of cytoskeletal proteins, (ii) processes controlling intercellular ion and water handling and membrane surface-to-volume ratio. All these factors may be disturbed in various forms of hereditary hemolytic anemia, such as sickle cell disease, thalassemia, hereditary spherocytosis and hereditary xerocytosis. Although mutations are known as the primary causes of these congenital anemias, little is known about secondary processes affecting RBC deformability. These secondary processes could however play an important role in the premature removal of the aberrant RBCs by the spleen. Altered RBC deformability could contribute to disease pathophysiology in various disorders of the RBC. Here we review the current knowledge on RBC deformability in different forms of hereditary hemolytic anemia and describe secondary mechanisms involved in RBC deformability.